Pengaruh Aktivitas Belajar Siswa Menggunakan Model Problem Based Learning Terhadap Kemampuan 4c (Collaboration, Communication, Critical Thinking, Creative Thinking) Siswa Pada Materi Sistem Pernapasan Di SMA - Assayidiyah, Bahiyatul Firdausy; Arip, Asep Ginanjar; Nur, Sofyan Hasanuddin (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2021)
The background of this research is Biology material about respiratory system' disease and disorders has not be linked to problems relevant on Students' life, Students' 4C capabilities are a global demand and students learning Activities have not fully paid attention to schools. Therefore, researcher tried to connect Students' Learning activities with Students' 4C capabilities in learning. The purpose of this study is to determine the effect of Students' learning activities using Problem Based Learning Model on 4C (Collaboration , Communication, Critical Thinking Creative Thinking) the capability of Students on Respiratory System Material. The research method used an experimental design. The population in this study are all students of class XI IPA at SMAN 1 Sukagumiwang in 2020/2020, the sampling technique is purposive as many as 20 students. Data collection techniques using tests, observation, quistionaires and documentation. Data analysis techniques used statistical and Multivariate Canonical Correlation. The results of this study are (1) Students learning activities using the PBL mod which has an effect on Students' 4C capabilities with an eigenvalue of 46.5 and the deoendent variabkr redudancy index explained by the independent Canonical variate of 97.8% and the independent variabkr redundancy index explained by the variable itsel. The dependent Canon is 68.5%, the eigenvakues indicate that the high level of learning activity Will affect the Students' 4C capabilities.